Factors affecting movement pattern of Sumatran elephant in Air Rami Production Forest, Bengkulu, Indonesia - NADYA LAKSMITHA; YANTO SANTOSA; Dede Aulia Rahman (Society for Indonesian Biodiversity, 2023)
Abstract. Laksmitha N, Santosa Y, Rahman DA. 2023. Factors affecting movement pattern of Sumatran elephant in Air Rami Production Forest, Bengkulu, Indonesia. Biodiversitas 24: 5539-5546. The decline in the quality and quantity of elephant natural habitat is a trigger factor for human-elephant conflict and results in a decrease in the elephant population. Research related to movement and habitat factors determining elephant movement is important to obtain information that can be used as a basis for conflict management and mitigation in the long term. We analyzed collared GPS data from a female adult elephant (n=1) in Air Rami Production Forest with recordings from November 2020 to August 2022. This study aims to investigate the relationship between the Sumatran elephant’s daily movement distance and movement period with habitat factors. The data obtained were analyzed using multiple regression analysis with tested variables, including secondary forest land cover, altitude, slope, distance from water sources, settlements, roads, and daily movement distance/movement period. The results showed that secondary forest land cover, slopes, movement period, distance from water sources, settlements, and roads influence the elephant's daily movement distance. Meanwhile, the relationship between the movement period is only influenced by slopes, distance from settlements and roads, and daily movement distance. Our study further provides information recognizing the preferred habitat factor of the Sumatran elephant, which gives stakeholders an essential tool for conservation.